Asymmetric parasitic twins - Heteropagus - Alves,Rita de Cássia S. (2020)
SUMMARY BACKGROUND: Asymmetric or heteropagus conjoined twins is a rare occurrence, with an incidence of one case in 1-2 million. Conjoined twins are classified according to their symmetry, place of fusion, and grade of duplication. METHODS: We report here an extremely rare presentation of parasitic twins not described before. We describe macro and micro anatomic alterations and discuss the aspects of this peculiar presentation and the importance of prenatal diagnosis. RESULTS: The case of a twenty-three-year-old patient, with monochorionic, monoamniotic asymmetrically-conjoined twin pregnancy, discovered at 29 weeks of gestational age. We believe that this report calls attention to this presentation and the importance of prenatal care and management. The twins were delivered vaginally without life. The twins’ combined weight was 1.300 gr. They were bonded in the left cervical region. CONCLUSION: This report may help to find strategies for clinical decisions in future cases. Antepartum diagnosis is important to the management, preoperative planning, and outcomes. Prenatal imaging exams like echocardiography, CT, MRI, and ultrasonography are feasible and can provide relevant information about malformation severity and prognosis.